Key metabolic and enzymatic adaptations underlie the benefits of formulated diets in the adult female Chinese mitten crab Eriocheir sinensis. (30th August 2020) - Long, Xiaowen; Sun, Yunfei; Wade, Nicholas M.; Pan, Jie; Liu, Yuming; Cheng, Yongxu; Wu, Xugan
Abstract: Natural and traditional diets have been gradually replaced with formulated diets for the Chinese mitten crab Eriocheir sinensis culture, but it is unclear what effects different feeding modes have on digestive physiology and metabolism of E. sinensis . This study investigated the effects of three feeding modes, formulated diets (FD), natural diets (ND, trash fish and freshwater snails) and traditional diets (TD, soybean, wheat, broad bean and corn) on digestive enzyme activity, physiological indices and metabolomics of adult female E. sinensis . The ND had the highest activities of trypsin and lipase in the hepatopancreas, while the highest amylase activity was detected in TD. The highest content of hepatopancreas triglyceride was detected in FD, while the highest levels of lipoprotein lipase, hepatic lipase, lactic acid, malonaldehyde, acid phosphatase and alkaline phosphatase in the hepatopancreas, as well as the total cholesterol, high‐density lipoprotein cholesterol, low‐density lipoprotein cholesterol and γ‐glutamyltransferase in serum were detected in ND. The TD had the highest content of glucose and uric acid in the hepatopancreas as well as the free cholesterol, lactic acid, aspartate aminotransferase and alanine aminotransferase in the serum. The metabolomics showed that most differential metabolites involved in amino acid anabolism in serum and hepatopancreas were significantly up‐regulated in FD. The metabolites involved in energy metabolism and gluconeogenesis in the hepatopancreas were significantly down‐regulated in FD. These results suggested that feeding with formulated diets promotes amino acid synthesis and reduces energy metabolism, which leads to more protein and glucose deposition in tissue.